Lectotypification of Artemisia mongolica (= A. vulgaris var. mongolica, Asteraceae) - Mosyakin, Sergei L.; Boiko, Ganna V.; Verloove, Filip (Phytotaxa, 2017)
Artemisia mongolica, initially described as A. vulgaris var. mongolica, is lectotypified by a specimen annotated by Besser (the author of the basionym) that originated from Fischer’s herbarium and is deposited in the Besser Memorial Collection at KW, with three isolectotypes in LE. An earlier neotypification by Filatova (2003) is therefore unnecessary. Further nomenclatural and historical notes are provided on the original material and publication of the name.